[LB.03.06] ATTENUATION OF SPLANCHNIC AUTOTRANSFUSION FOLLOWING NON-INVASIVE ULTRASOUND RENAL DENERVATION: A NOVEL MARKER OF PROCEDURAL SUCCESS. (September 2017) - Saxena, M.; Shour, T.; Shah, M.; Wolff, C.; Collier, D.J.; Kapil, V.; Balawon, A.; Pheby, J.M.; Zak, A.; Julu, P.; O'Brien, B.; Schmieder, R.; et al.
Abstract : Objective: In the Valsalva manoeuvre, autotransfusion in Phase IIi arises from sympathetically mediated capsular contraction of intra-abdominal organs including the kidneys. We hypothesised that following successful renal nerve ablation this response would be attenuated and could serve as a marker of procedural success. Design and method: 23 patients (mean age 59.4 ± 10.5 years; BMI 30.2; anti-hypertensive medication 4.2; 65% males and 35% females) with resistant HTN (On 3 or more anti-hypertensive drugs including a diuretic) were enrolled in the double-blind, sham controlled KONA Wave IV study. They were randomised either to bilateral RDN using therapeutic levels of ultrasound energy (n = 12, 75% male, mean age 57.2 ± 10.3 years) or the sham procedure using bilateral application of diagnostic levels of ultrasound energy (n = 11, 55% male, mean age 61.9 ± 10.6 years). Within group changes in autonomic parameters, office blood pressure (OBP) and ambulatory BP (ABP) were compared between baseline and 6 months in a double blind manner. Results: There was significant OBP reduction in both treatment (16.1 ± 27.3 mmHg, p < 0.05) and sham groups (27.9 ± 15.0 mmHg, p < 0.01). In the treatment group, heart rate (HR) was significantly reduced following RDN both at rest (4.3 ± 6.6 bpm, p < 0.05) and in response to postural changes. During phase IIi Valsalva, RDN resulted in substantial and significant reduction in MAP (21.8 ± 25.2 mmHg, p < 0.05) with no significant changes in the sham group. Figure. No caption available. Conclusions: BP reduction per se is not necessarily a marker of renal nerve ablation. Reduction in splanchnic auto-transfusion following RDN has not been previously demonstrated and denotes attenuation of (renal) sympathetic efferent activity and could serve as a marker of procedural success. Sham therapy results in clinically meaningful BP reduction that has implications for future trial design.